2000
DOI: 10.1023/a:1006407314449
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Pheophytin a (Pheo) in Photosystem II reaction centres was exchanged for 13(1)-deoxo-13(1)-hydroxy-pheophytin a (13(1)-OH-Pheo). The absorption bands of 13(1)-OH-Pheo are blue-shifted and well separated from those of Pheo. Two kinds of modified reaction centre preparations can be obtained by applying the exchange procedure once (RC(1x)) or twice (RC(2x)). HPLC analysis and Pheo Q(X) absorption at 543 nm show that in RC(1x) about 50% of Pheo is replaced and in RC(2x) about 75%. Otherwise, the pigment and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
43
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 10 publications
12
43
0
Order By: Relevance
“…It is also unlikely that both pheophytins contribute to the absorption near 676-681 nm region as proposed in Refs. 7,33,41,42 In contrast, we have demonstrated that the Q x -/Q y -region site-energies of Pheo D1 and Pheo D2 are most likely at ~545/~680 nm and ~541.5/~670 nm, respectively, in good agreement with our previous assignment. 26,34 These values should be used to model excitonic structure and excitation energy transfer dynamics of the PSII RC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is also unlikely that both pheophytins contribute to the absorption near 676-681 nm region as proposed in Refs. 7,33,41,42 In contrast, we have demonstrated that the Q x -/Q y -region site-energies of Pheo D1 and Pheo D2 are most likely at ~545/~680 nm and ~541.5/~670 nm, respectively, in good agreement with our previous assignment. 26,34 These values should be used to model excitonic structure and excitation energy transfer dynamics of the PSII RC.…”
Section: Discussionsupporting
confidence: 91%
“…Here we only note that the ratio of the nonresonant TBHB spectrum (I = 100 mW) to NPHB (saturated persistent hole) in spinach (see Figure 3) is about 3.5, while the same ratio in C. reinhardtii (obtained under identical conditions; see Figure 3) is about 5.5. Interestingly, the ratio of ~3.6 was also observed in destabilized P680-type RCs 7,41 , which suggested that both pheophytins have their Q y absorption maxima at 676-680 nm (at 6 K), are inconsistent with data shown above. In addition, the blue shift of both the Q x and Q y transitions of Pheo D1 in destabilized RCs (see Figure S1; Supporting Information) is consistent with resonance Raman spectroscopy data 69 , where it was suggested that Pheo D1 in the PSII RC is likely H-bonded (as BPheo L in the BRC 70,71 ), with the glutamine residue D1-Gln130 being the likely homologue of the glutamic acid residue L-104 in BRC.…”
Section: The Only Difference Between (Nonresonant) Saturated Persistementioning
confidence: 64%
“…Cubic periodic boundary conditions were employed in all the simulations. To facilitate the analysis, the position of the droplet was fixed in the centre of the simulation box, and a global constraint was applied to fix the orientation of the director along the z axis [27].…”
Section: Molecular Model and Simulation Methodsmentioning
confidence: 99%
“…By subtracting scaled spectra of the two preparations, it is evident that the accessory chl a removed upon forming the 5-chl a preparation absorbs near 670 nm and has no MCD 'deficit'. The observation of a pronounced MCD 'deficit' in D1/D2/cyt b 559 preparations, peaking where bleaches are characteristically seen [18,19], points to the utility of this method as a P680 fingerprint. An extended theoretical base for the MCD of coupled pigments [20] may assist in more detailed assignments of pigments in fully active PSII.…”
Section: Article In Pressmentioning
confidence: 95%